General medicine, first-line medicine in Morocco: How is it perceived by medical students and how to enhance their interest in this career? - Maryam Fourtassi; Abda Naima; Yassamine Bentata (AOSIS, 2021)
In Morocco, family medicine does not exist, and it is general medicine that plays the role of family medicine and is also first line medicine and primary care. The current medical school curriculum is not fully in harmony with the real health needs of the population. We questioned 6th and 7th year students about the pertinence of two rotations in general medicine, that is, in a health centre and a private practice, via an anonymous questionnaire disseminated online in June 2020. A total of 266 responses were collected. Out of these, 41.5% of responses were enrolled in 6th year, versus 58.5% in 7th year. Then, 59.1% of students were females. In addition, 84.8% of them declared their intention to pursue a career in a medical specialty, whereas only 15.2% of them were interested in a career as a general practitioner. Notably, 67.4%, 26.5% and 6.1%, respectively, thought that general medicine was very undervalued, a little undervalued and not undervalued. It should be noted that 3.8%, 44.1% and 52.1%, respectively, were interested, somewhat interested and not at all interested in family medicine as a specialty if it was implemented. To that end, various actions need to be undertaken, including the introduction of quality teaching in the 6th and 7th years of medical studies, focused on the development of the knowledge and skills required, the strengthening of pre-existing practical training periods in public health and the introduction of a rotation in private practices of general medicine.